Compartment syndrome after viper-bite in toddler: case report and review of literature - Pietrangiolillo, Z.; Frassoldati, R.; Leonelli, et al., V. (Acta Biomedica Atenei Parmensis, 2012)
Snakebites in Italy are a rare source of severe medical condition, except in case of venomous snakes. The venom causes both local and/or systemic complication which may determine death in 6-60 hours, particularly in children and the elderly. In fact, the same amount of venom affects children more severely than adults because of the reduced total dilution volume in children. The only specific and conflicting therapy for venomous snakebite is to administer the appropriate anti-venom; the remaining therapy is symptomatic and supportive.We describe the case of a 22 months old child who, despite appropriate symptomatic treatment, developed severe signs and an acute compartment syndrome of the right upper limb, a rare complication of venom snakebite. Administration of antivenom and fasciotomy were needed to resolve the acute episode permitting a positive outcome. On the basis of literature review and our experience we hypothesize an algorithm for the treatment of these patients.